A peculiar case of idiopathic orbital myositis in adolescence: Poster Presentation - Case Report - Resident - NABILA ALJUFRI; Agung Nugroho; Sita Paramita; Salmarezka Dewiputri; M. Sidik; Syntia Nusanti (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Idiopathic orbital myositis, an inflammation localized at the extraocular muscles, is rarely reported in pediatrics. Until now, the prevalence and incidence of orbital myositis remain unknown. This paper aims to report a case of idiopathic orbital myositis in a young girl with headache. Case Illustration : A-16-year-old presented with a droopy eyelid of the left eye (LE) and double vision since 1 week before admission. She also experienced swollen eyelid and cluster headache for 5 months with no neurological abnormalities. Ophthalmic examinations showed exotropia with limited eye movement of LE. Ptosis of LE was noted with margin reflex distance 1 (MRD-1) +2 mm, while MRD-1 +6 mm for the right eye. Other examinations were unremarkable with normal funduscopy and negative RAPD. Non-contrast orbital sinus CT-Scan revealed an enlargement of the superior rectus and lateral rectus muscle. The laboratory result showed slight leucocytosis and normal ESR. High-dose intravenous corticosteroid was administered and tapered with oral steroid. The orbital clinical findings showed improvements, better ocular movements, and diminished headache complaints. Discussion : As a rare case, the diagnosis of orbital myositis in adolescence can be challenging and requires detailed examination, and proper imaging to exclude other diagnosis such as ophthalmoplegic migraine, infections, malignancies, or congenital lesions (hemangioma). The first-line therapy is a systemic corticosteroid, which well responded in this patient. Conclusion : In this patient, intravenous corticosteroid represent an effective treatment. Close monitoring of the disease progression is required after switching to oral therapy to prevent relapse.